2022
DOI: 10.3390/cryst12101418
|View full text |Cite
|
Sign up to set email alerts
|

Biological Mineralization of Hydrophilic Intraocular Lenses

Abstract: Biomaterials calcify upon implantation in contact with biological fluids, which are supersaturated with respect to more than one crystalline phase of calcium phosphate. The implantation of intraocular lenses (IOLs) for cataract treatment has been hailed as a major advance. Hydrophilic acrylic IOLs, made of Poly(2-hydroxyethyl methacrylate) (PHEMA), upon contact with aqueous humor, exhibit significant incidence of opacification, due to the formation of calcium phosphate crystals, mainly hydroxyapatite (Ca5(PO4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…As may be seen, along with the increasing GO concentration of the suspensions equilibrated with HAP, which resulted in a higher GO retention by the crystals (confirmed by the TGA analysis, which showed proportionally higher mass loss at the temperature domain between 300 and 450 °C), the crystal growth rate of the hydroxyapatite (HAP) formation also increased. The increase in the crystal growth rate up to equilibration with 10 The morphology of HAP crystals grown at constant supersaturation was the same as reported earlier for the PHEMA IOLs and consisted of prismatic HAP nanocrystals [10][11][12], as shown in the SEM photos in Figure 17. × 10 −4 % w/v concentration of GO suspension showed a tendency to level off; however, for the solid equilibrated with 20 × 10 −4 % w/v GO suspension, the rate of crystal growth increased dramatically.…”
Section: Mineralization Experimentssupporting
confidence: 77%
See 2 more Smart Citations
“…As may be seen, along with the increasing GO concentration of the suspensions equilibrated with HAP, which resulted in a higher GO retention by the crystals (confirmed by the TGA analysis, which showed proportionally higher mass loss at the temperature domain between 300 and 450 °C), the crystal growth rate of the hydroxyapatite (HAP) formation also increased. The increase in the crystal growth rate up to equilibration with 10 The morphology of HAP crystals grown at constant supersaturation was the same as reported earlier for the PHEMA IOLs and consisted of prismatic HAP nanocrystals [10][11][12], as shown in the SEM photos in Figure 17. × 10 −4 % w/v concentration of GO suspension showed a tendency to level off; however, for the solid equilibrated with 20 × 10 −4 % w/v GO suspension, the rate of crystal growth increased dramatically.…”
Section: Mineralization Experimentssupporting
confidence: 77%
“…The apparent conclusion is that the presence of GO on HAP crystals resulted in the enhancement of the active crystal growth sites, possibly via the contribution of the ionized carboxyl groups of GO. The morphology of HAP crystals grown at constant supersaturation was the same as reported earlier for the PHEMA IOLs and consisted of prismatic HAP nanocrystals [10][11][12], as shown in the SEM photos in Figure 17. Next, hydrophilic IOLs modified via equilibration with GO suspensions, both before and after reduction with phenyl hydrazine, were investigated.…”
Section: Mineralization Experimentssupporting
confidence: 56%
See 1 more Smart Citation
“… 1 However, the potential of an IOL material to be transparent must be taken into consideration when evaluating the long-term biocompatibility of the material, particularly for the hydrophilic acrylic IOLs, which are at a higher risk of developing calcification of the lens material. 2 4 Here, we present the clinical and laboratory characteristics of an unusual case of hydrophilic IOL opacification 23 years after a successful phacoemulsification procedure due to traumatic cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels of this type are extensively used for the fabrication of biomaterials. Recent studies suggested that PHEMA promotes nucleation and growth of hydroxyapatite (Ca5(PO4)3OH, HAP) upon contact with solutions supersaturated with respect to HAP [10][11][12].…”
Section: Introductionmentioning
confidence: 99%